Cert Prep: Unity Certified Associate Game Developer Scripting with C#. - Thorn, Alan (linkedin.com, 2021)
Learn how to build C# scripts to make intelligent game objects and NPCs, and prepare for the scripting and publishing portion of the Unity Certified Associate: Game Developer exam.